PENGARUH MOBILE TRUST DAN MOBILE SATISFACTION TERHADAP ELECTRONIC WORD OF MOUTH DAN NIAT MENGGUNAKAN GOPAY - Vito Lifa Meisyah Putra; Meta Andriani (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to analyze the influence of Mobile Trust and Mobile Satisfaction on Electronic Word of Mouth (EWOM) and the intention to use e-wallets, focusing on the GoPay application. The method used is quantitative, with data collection through a survey questionnaire involving 100 Generation Z respondents aged 19 to 23 years. The analysis results using Partial Least Squares (PLS) indicate that Mobile Trust has a positive and significant impact on EWOM, while Mobile Satisfaction does not show a significant effect. On the other hand, Perceived Risk has been proven to positively influence the intention to use e-wallets. An interesting aspect of this hypothesis is that Generation Z tends to view high risk as a challenge. They see perceived risk not just as a barrier but as an opportunity to learn and grow, while Security significantly affects EWOM but not the intention to use e-wallets. This research underscores the importance of user trust in influencing the decision to share positive information about digital services. These findings provide insights for e-wallet service providers to develop more effective marketing strategies, focusing on enhancing Mobile Trust and service security.